Alteration of extracellular enzyme activity and microbial abundance by biochar addition: Implication for carbon sequestration in subtropical mangrove sediment. (1st November 2016) - Luo, Ling; Gu, Ji-Dong
Abstract: Biochar has attracted more and more attention due to its essential role in adsorbing pollutants, improving soil fertility, and modifying greenhouse gas emission. However, the influences of biochar on extracellular enzyme activity and microbial abundance are still lack and debatable. Currently, there is no information about the impact of biochar on the function of mangrove ecosystems. Therefore, we explored the effects of biochar on extracellular enzyme activity and microbial abundance in subtropical mangrove sediment, and further estimated the contribution of biochar to C sequestration. In this study, sediments were amended with 0 (control), 0.5, 1.0 and 2.0% of biochar and incubated at 25 °C for 90 days. After incubation, enzyme activities, microbial abundance and the increased percentage of sediment organic C content were determined. Both increase (phenol oxidase and β-glucosidase) and decrease (peroxidase, N-acetyl-glucosaminidase and acid phosphatase) of enzyme activities were observed in biochar treatments, but only peroxidase activity showed statistical significance (at least p < 0.01) compared to the control. Moreover, the activities of all enzymes tested were significantly related to the content of biochar addition (at least p < 0.05). On the other hand, bacterial and fungal abundance in biochar treatments were remarkably lower than control ( p < 0.001), and the significantly negative relationship ( p < 0.05) between bacterial abundance and the content of biochar was found. Additionally, the increased percentage of organic C gradually increased with biochar addition rate, which provided evidence for applying biochar to mitigate climate change. Given the importance of microorganisms and enzyme activities in sediment organic matter decomposition, the increased C sequestration might be explained by the large decrease of microbial abundance and enzyme activity after biochar intervention. Graphical abstract: This results provided the evidence that biochar addition could enhance C sequestration in coastal mangrove sediment, and also suggested that the reduced microbial abundance and enzyme activity might explain the decreased decomposition of sediment organic matter. Highlights: Extracellular Enzyme activity in mangrove sediment is significantly affected by biochar addition. Microbial abundance decreased after biochar addition in mangrove sediment. Sediment organic carbon increased with biochar addition in mangrove sediment. Biochar application may mitigate climate change through affecting enzymatic and microbial activity.